Translating research into practice: Lessons from trials of thrombolysis in acute stroke - Venables, Graham (Medknow Publications, 2008)
There exist individual, institutional and national barriers to change, none more so than when introducing new therapies into medical practice especially those that involve organizational change. This paper, presented as an address to the joint meeting of the Association of British Neurologists and the Indian Academy of Neurology in October 2007, explores these barriers in the context of the instruction of thrombolytic therapy for patients with acute ischaemic stroke and suggests how they might be overcome using evidence from relevant clinical trials and observational studies.